Evaluation of Suppliers in the Implementation of Sustainable Supply Chains for the Apparel Industry in Indonesia - Rosalin, Gustina; Santosa, Wahyuningsih (Journal of Social Research, 2023)
In the context of globalization, the development and management of operations related to products and services are becoming more complex, stakeholders are demanding and aware of the challenges of sustainability along the supply chain. One of them is the clothing industry which is a global industry that provides basic human needs and is one of the industrial sectors that has an impact on the environment and society. To address the risk and opportunity issues of sustainability from an industry and value chain perspective, apply the concept of sustainable supply chain management (SSCM). This study aims to design an instrument in the form of a minimum standard to measure supplier performance and analyze it. Using a qualitative analysis method resulting from due diligence on suppliers with a total of 77 question points consisting of 23 questions on the environmental dimension, 23 questions on the social dimension related to employment, and 26 questions related to governance. The results show that 3 suppliers are at the High-performance level, 4 companies are in the Medium-performance category, 5 are companies with low performance and 1 company is in the very low category. By categorizing the highest total gain of ESG, namely 100%, and the lowest score of 34.62%. This value indicates the level of compliance with the minimum standards set. Recommendations for Further Research An even number of due diligence is carried out for categories in the fashion industry (clothing, hats, bags, footwear). The aspects and weights of each of these sustainability aspects can be re-analyzed if used for other types of industries outside the fashion industry.